Delik Penghinaan dan Beberapa Aspeknya Studi Perbandingan Antara Indonesia dan Amerika - Lesmana, Tjipta (LAW REVIEW, 2006)
Press freedom in Indonesia enjoys euphoria following the downfall of Soeharto regime in May 1998. Embarking libertarian theory Indonesia press is putting heavily its function as watchdog, monitoring and supervising all aspects of life in the nation, notably government activities. But the radical change in press life was generally viewed with high discontent among people. They regard the phenomenon as "too luxurious " and cannot be afforded by people 60% of them are uneducated and poor. Various negative impacts were detected during the past 5 years of liberal press experiment. Some journalists, for example, have tendency to recklessly write their reports which defame others and bring law suit in the court. No less than 20 libel cases were trialed since 1998. Publishers and journalists were mostly lost the cases, being heavily fined or threatened to be imprisoned. Some journalists are worried that they become the target of litigation for libel, making accusation that press freedom in the country is currently in a bad shape. Is press trial indeed threatening freedom of the press? This is the research question. It is a qualitative study, using content analysis to collect the data required. About 20 libel cases, 10 in Indonesia and 10 in United States, were carefully investigated. Special attention was paid on 9 aspects of libel case, i.e. correction right (hak jawab), denial right (hak tolak), public interest, public figure, news source, right quotation, true/false report, check-andbalance, Â and malice or reckless disregard of the truth. Textual unit analysis is applied, especially views delivered by judges, journalists, and experts in journalism. Comparative study was applied to understand similarities and differences of opinions in both countries.